Sniffing behaviour, copulatory readiness, copulatory performance and reproductive morphology of adult male rats weaned prematurely - Hlinák, Z; Gandalovicová, D; Roth, Z (Physiologia Bohemoslovaca, 1989)
Sexual behaviour of adult male rats weaned prematurely--on day 15 after birth--and of males weaned at the optimal age--on day 28--was compared at two life periods: at the age of 90 days and when the males were one year old. Sexual behaviour was evaluated by means of three characteristics: a) sniffing behaviour, b) copulatory readiness, c) copulatory performance. The differences in sniffing behaviour between prematurely and normally weaned males were assessed in terms of their responsiveness to sccents of unrelated adult males or oestrous females and from the point of view of both housing conditions after weaning and the animals' sexual experience. No differences were found in copulatory readiness as well as in copulatory performance between the two groups of males tested in their interaction with a female exhibiting complete precopulatory pattern. The morphological examination revealed no differences in the weight of reproductive organs and in spermatozoa development. We conclude that the sexual behaviour as well as reproductive organs of male rats are very resistant to early separation of pups from the mother which contrasts with some earlier findings.
Keywords: inbrední kmeny potkanů; Rats, Inbred Strains; Rats; kopulace; sexuální chování zvířat; mužské pohlaví; testis; krysa rodu Rattus; Body Weight; Copulation; Organ Size; Weaning; velikost orgánu; ženské pohlaví; zvířata; Spermatogenesis; tělesná hmotnost; odstavení; Female; Sexual Behavior, Animal; spermatogeneze; Testis; Male; Animals